2019
DOI: 10.1016/j.jacr.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Thyroid Disease

Abstract: There are a wide variety of diseases that affect the thyroid gland ranging from hyperplastic to neoplastic, autoimmune, or inflammatory. They can present with functional abnormality or a palpable structural change. Imaging has a key role in diagnosing and characterizing the thyroid finding for management. Imaging is also essential in the management of thyroid cancer.The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
0
14
0
1
Order By: Relevance
“…Pre-contrast CT scans are useful for the detection of calcifications and ectopic thyroid tissues and for differentiating tumor recurrence from remnant thyroid tissue after thyroidectomy [ 21 233 ]. A contrast-enhanced CT is mandatory to assess LN metastases, which are seen as areas of strong or heterogeneous enhancement and cystic changes [ 21 234 ]. Based on studies of iodine retention, contrast media is not contraindicated in patients with thyroid cancer.…”
Section: Role Of Ct In Thyroid Cancer Diagnosismentioning
confidence: 99%
“…Pre-contrast CT scans are useful for the detection of calcifications and ectopic thyroid tissues and for differentiating tumor recurrence from remnant thyroid tissue after thyroidectomy [ 21 233 ]. A contrast-enhanced CT is mandatory to assess LN metastases, which are seen as areas of strong or heterogeneous enhancement and cystic changes [ 21 234 ]. Based on studies of iodine retention, contrast media is not contraindicated in patients with thyroid cancer.…”
Section: Role Of Ct In Thyroid Cancer Diagnosismentioning
confidence: 99%
“…However, current study showed that eye manifestations were nearly similar in the GD and TMNG groups. The American College of Radiology Appropriateness Criteria Thyroid Disease stated that thyroid scanning as a diagnostic tool is not appropriate in the following cases: hypothyroid state, euthyroid state with palpable nodule but no goiter, and preoperative evaluation of thyroid cancer in euthyroid patients [30]. Despite these recent guidelines, our study showed that thyroid scans are inappropriately ordered for 8.2% of patients who were euthyroid and for 3.3% of patients who were hypothyroid at the time of the scan.…”
Section: Discussionmentioning
confidence: 59%
“…There is consensus that autonomous nodules have a low RoM (Perros et al 2014, Gharib et al 2016, Haugen et al 2016, Russ et al 2017, Pacini et al 2018, Hoang et al 2019, Giovanella et al 2019. Scintigraphy with 123 I or 99m Tc might be indicated for individuals with thyroid nodules in three situations.…”
Section: Scintigraphy With 123 I or 99m Tcmentioning
confidence: 99%
“…Scintigraphy with 123 I or 99m Tc might be indicated for individuals with thyroid nodules in three situations. This method is recommended in patients with low TSH (Perros et al 2014, Gharib et al 2016, Haugen et al 2016, Russ et al 2017, Pacini et al 2018, Hoang et al 2019, Giovanella et al 2019, even if they are asymptomatic and have normal free T4 and T3 concentrations. Many authors even recommend this method in euthyroid individuals with TSH in the lower half of the reference range, especially in iodine-deficient regions (Gharib et al 2016, Russ et al 2017, Giovanella et al 2019.…”
Section: Scintigraphy With 123 I or 99m Tcmentioning
confidence: 99%
See 1 more Smart Citation